A new species and notes on unusual natural history of Cladochaeta Coquillett, 1900 (Diptera: Drosophilidae) - Carvalho-Filho, Fernando Da Silva; Pirani, Gabriela; Kloss, Thiago Gechel (Zootaxa, 2018)
A new species of Cladochaeta Coquillett (Diptera: Drosophilidae) is described, C. caxiuana sp. nov. from the Brazilian Amazon, based on 10 male and 10 female specimens obtained from nymphs of Sphodroscarta trivirgata (Amyot & Serville, 1843) (Hemiptera: Auchenorrhyncha: Aphrophoridae). The female of Cladochaeta atlantica Pirani & Amorim, 2016 is described based on specimens reared from spider egg sacs of the spider Cryptachaea migrans (Keyserling, 1884) (Araneae: Theridiidae) obtained in the state of Espírito Santo, Brazil. This is the first record of this fly genus attacking a spider egg sac. The species Cladochaeta sororia (Williston, 1896) is recorded for the first time from Brazil, based on specimens collected in an urban garden in the Amazon. In addition, an unidentified female specimen of Cladochaeta Coquillett, 1900 was obtained from the cocoon of a spider wasp of the genus Notocyphus Smith (Hymenoptera: Pompilidae).